Effects of ecstasy on cooperative behaviour and perception of trustworthiness: A naturalistic study. (November 2014) - Stewart, LH; Ferguson, B; Morgan, CJA; Swaboda, N; Jones, L; Fenton, R; Wall, MB; Curran, HV
Background: Acute recreational use of 3, 4-methylenedioxymethamphetamine (MDMA; 'ecstasy') can promote pro-social effects which may alter interpersonal perceptions. Aims: To explore such effects, this study investigated whether acute recreational use of ecstasy was associated with changes in individual perception of trustworthiness of people's faces and co-operative behaviours. Method: An independent group, repeated measures design was used in which 17 ecstasy users were tested on the night of drug use (day 0) and again three days later (day 3); 22 controls were tested on parallel days. On each day, participants rated the trustworthiness of 66 faces, carried out three co-operative behaviour tasks (public good; dictator; ultimatum game) and completed mood self-ratings. Results: Acute ecstasy use was associated with increased face trustworthiness ratings and increased cooperative behaviour on the dictator and ultimatum games; on day 3 there were no group differences on any task. Self-ratings showed the standard acute ecstasy effects (euphoria, energy, jaw clenching) with negative effects (less empathy, compassion, more distrust, hostility) emerging on day 3. Conclusions: Our findings of increased perceived trustworthiness and co-operative behaviours following use of ecstasy suggest that a single dose of the drug enhances aspects of empathy. This may in turn contribute to its popularity as a recreational drug and potentially to its enhancement of the therapeutic alliance in psychotherapy.